Teaching the Introduction to Religions: Religious Pluralism in a Post- Colonial World. - Southard, Naomi; Payne, Richard (Teaching Theology & Religion)
Abstract. Taking seriously the implications of post-colonial theory, the authors revisit the introductory course (normally "World Religions") as a course on the plurality of religions in contemporary U.S. culture. They explain the structure of the course, and discuss practical and ethical issues around student field visits to learn about other religions.